The Role of Daily Physical Activities in Enhancing Subjective Well-Being Among Chilean School-Aged Children - Farias-Valenzuela, C (John Wiley and Sons Ltd, 2025)
This study aimed to examine the association between children s participation in physical and sports activities and their affective subjective well-being. Data were drawn from the Second Wave of the Children s Worlds: International Survey of Children s Well-Being (ISCWeB), involving a sample of 913 Chilean children aged 10 and 12 years. Participants completed self-report measures assessing feelings of happiness, sadness, stress, energy and boredom (positive and negative affect—CW PNAS). Participation in physical activities and sports was significantly correlated with positive well-being, indicating a strong link between such involvement and perceived positive affect. Age and gender did not significantly influence these outcomes. In contrast, lower participation in physical and sports activities was significantly associated with higher negative affect, with neither age nor gender showing substantial impact on this result. This research employed structural equation modelling to develop a model measuring physical and sports activities (PSA) and subjective well-being in Chilean schoolchildren. The study confirms the model s effectiveness in explaining the relationship between children s SWB and PSA involvement. Analysis showed significant correlations between indicators and emotional well-being factors. Findings emphasise emotions like calmness, happiness and stress in understanding the affective dimensions of children s well-being related to PSA. © 2025 The Author(s). Infant and Child Development published by John Wiley & Sons Ltd.